The Use Of Temporary Towers To Optimize The Completion Of Reconductoring And Tower Replacement Of 150 Kv High Voltage Overhead Lines (SUTT) - Muhammad Iqbal (PT. Publikasiku Academic Solution, 2023)
Transmission lines play an important role in the successful and stable operation and distribution of power grids both for power evacuation from power plants and as a link from one Substation to another. The construction of new transmission lines as a form of meeting high electricity needs in the current era of Globalization has many obstacles, both in terms of rejection from residents, expensive licensing arrangements, and very expensive investment costs. Reconductoring is one of the methods of increasing transmission capacity at minimum cost with an adequate level of quality and reliability. Reconductoring is the best solution today to increase conductor conducting capacity with the least investment and get maximum economic efficiency. However, considering that reconductoring is an addition of transmission capacity using old or existing lines and also requires tower replacement, so an outage with a long duration is needed which is feared to have an impact on system reliability. Therefore, the use of emergency towers is believed to be a solution to shorten the blackout time. Emergency towers are used as tools in reconductor work and tower replacement. A study was conducted by calculating the Cost Budget Plan (RAB) and schedule analysis using the Microsoft Project Application to determine the comparison of the duration of time needed to complete reconductoring work and tower replacement between using an emergency tower and without an emergency tower. From the time schedule made, it will be known which work method uses a shorter duration of time so that it can save or speed up the blackout time. This study is expected to produce a shorter schedule of reconductoring and tower replacement work using temporary/emergency towers and with a smaller RAB compared to Total Operating Costs so as to shorten the duration of the outage time at an efficient cost.